Meeting the need for corrective spectacles in visually impaired Chinese school children: the potential of ready-made spectacles. Issue 8 (2nd October 2018) - Zhu, Zhuoting; Ellwein, Leon B; Wang, Sean K; Zhao, Jialiang; He, Mingguang
Abstract : Purpose: To assess the potential of ready-made (spherical) spectacles (RMS) in meeting the need for refractive correction in visually impaired children in China. Methods: Eligible children aged 5–17 years were identified from the three study sites in China. Distance visual acuity was measured with a retroilluminated logarithm of the minimum angle of resolution chart with tumbling E optotypes. Cycloplegic autorefraction was performed on all children using a handheld autorefractor. If uncorrected visual acuity (UCVA) was ≤20/40 in either eye, best corrected visual acuity was measured with subjective refractive error. Results : A total of 13 702 children were enumerated from the three studies, with 12 334 (90.0%) having both reliable visual acuity measurements and successful cycloplegia. Among the 12 334 study children, the prevalence of UCVA ≤20/40 in the better seeing eye was 16.4% (95% CI 15.0% to 17.8%), with 91.1% (1843) of these improving by ≥3 lines of visual acuity with refractive correction. Prevalence was 12.7% (95% CI 11.5% to 13.9%) for UCVA < 20/50 with 97.4% (1521) improving by ≥3 lines, and 9.38% (95% CI 8.39% to 19.4%) for UCVA ≤20/63 with 98.4% (1138) improving by ≥3 lines. Depending on the severity of visual impairment, 62.8%–64.0% of children could be accommodated with RMS if not correcting for astigmatism of ≤0.75 dioptres and anisometropia of ≤0.50 spherical equivalent dioptres. Approximately 87% of children could be accommodated with RMS if astigmatism and anisometropia limits were increased to ≤1.25 and ≤1.50 dioptres, respectively. Conclusions: RMS could substantially alleviate visual morbidity in two-thirds or more of visually impaired schoolchildren in China. This cost-effective approach to refractive correction might also be useful in low/middle-income countries with poor access to optometric services.